DINAMIKA PENGELOLAAN WAKAF DAN POTENSI PENGEMBANGAN EKONOMI DI MESIR - Kasdi, Abdurrahman (ZISWAF, 2016)
AbstractManagement of waqf professionally will be able to empower potential productive endowments. Endowments have played an important role in driving the economy and meet the needs of Egyptian society. Pioneers first waqf in Egypt was a judge in the era of Hisham bin Abdul Malik, named Tauba bin Namir al-Hadrami who became a judge in the year 115 H. He is donating the land to build the dam and its benefits are developed productively for the benefit of the people. Wakaf pioneered by Tauba this very rapid growth, and even become a major asset for the people of Egypt. Efforts to modernize Egypt endowments managed by the issuance of Law No. 48 Year 1946 regarding waqf law covering the terms of endowments and endowment. Then in 1971 published Law No. 80 that inspired the establishment of an Egyptian Waqf Board specifically address the issue of endowments and development. Egyptian Waqf Board referred to in this law then promulgated by decree of the President of Egypt on 12 Sha'ban 1392 AH (20 September 1972), which is responsible for doing the same work and empower endowments, in accordance with the mandate of the law and the program of the Ministry Egyptian Endowments. Waqf Board's task is to coordinate and implement all the distribution of endowments, as well as all activities perwakafan to comply with the objectives set by the Shari'ah.